Digital reconstruction hypothesis of the Roman‐era fluvial barge from Kamensko, Croatia - Zubčić, Krunoslav; Boetto, Giulia; Divić, Anton; Poveda, Pierre (Sailing through History. Reading the Past – Imagining the Future: Proceedings of the 16th International Symposium on Boat & Ship Archaeology ISBSA 16, 2024)
The Kamensko barge sank to the bottom of the Kupa River sometime between the 1st and 3rd centuries AD. Its well-preserved remains, discovered in 2009 on the riverbed in the vicinity of Karlovac in Croatia, were excavated between 2015 and 2018. The quantity and quality of the obtained documentation allowed the reconstruction hypotheses of its hull shape, structure and technical system to be proposed and modelled through an exclusively digital approach, whose outlines will be presented in the text below.